Increasing coastal reclamation by Invasive alien plants and coastal armoring threatens the ecological sustainability of coastal wetlands - Li, Jian; Leng, Zhanrui; Yuguda, Taitiya Kenneth; Wei, Lili; Xia, Jiaojiao; Zhuo, Chongyu; Nie, Ziying; Du, Daolin (Frontiers in Marine Science, 2023)
Coastal reclamation is becoming a common land restoration trend all over the world as a result of the rising demand for land. Though restoring coastal wetlands has significant economic advantages, a slew of adverse ecological effects threatens the carbon functions of coastal wetlands. For the objective of making appropriate land use policymaking, the ecological-economic trade-offs of reclamation initiatives must be carefully considered. In this study, we utilized appropriate models to estimate the ecosystem service values and economic benefits of invasive alien plants and embankment seawall coastal reclamation in China. We centered on three main ecology-related ecosystem services: greenhouse gas regulation, storm-flood-erosion control, and waste treatment/habitat preservation. Coastal reclamation intensity index and financial analysis were utilized to assess the trade-offs between ecological degradation and economic benefit resulting from land reclamation. Findings reveal that a total of 26,322 ha and 10,731 km of coastal wetlands were reclaimed by Spartina alterniflora and seawalls respectively from 2000 to 2020 in China. S. alterniflora reclamation resulted in a significant decline of ESV loss of 5,702,454 Yuan ha−1, while seawalls reclamation yielded some Ecosystem service value (ESV) gain of 4,800, 111 Yuan km-1 from 2000-2020. The combined effects of coastal armoring and invasive S. alterniflora reclamation led to a loss of about 32.2 billion Yuan in ESV for the study duration. Economic gains failed to make up for the ecosystem service value ESV loss, since the cumulative ESV loss significantly exceeded the economic gains across the period studied. This correlation of trade-offs emerged from reclamation development that favored quick economic gains over long-lasting ecological value, posing a potential long-term threat to the ecological integrity and carbon sinks in coastal wetlands. To establish an equilibrium between seawall reclamation and Invasive alien plant species spread in coastal wetlands, stakeholders could use this scientific knowledge as leverage to avert future irreparable losses.